Acerca del presunto (y discutible) origen mudéjar del autor del Taʾrij al-fattāš. About the Presumed (and Questionable) Mudejar Origin of the Author of the Taʾrīj Al-Fattāš. - Villar Iglesias, José Luis de (Historia. Instituciones. Documentos, 2019)
La familia Kati es una de las más notables de la ciudad de Tombuctú, posiblemente el centro político, económico y cultural más importante del África Occidental subsahariana a partir del siglo XIII. A esta familia perteneció el que ha sido generalmente considerado autor del Taʾrīj al-Fattāš, Maḥmūd Kāti. Esta crónica es una fuente esencial para el conocimiento de la historia del que los autores árabes medievales llamaron Bilād al-Sūdān, el País de los Negros. El objetivo de este artículo es revisar la tradición mantenida en el seno de la familia de que el padre de Maḥmūd Kāti, descendiente de un antiquísimo linaje andalusí, se instaló en el Sudán Occidental en el último tercio del siglo XV, procedente de la Península Ibérica. ABSTRACT: The Kati family happens to be one of the most dignitary in the city of Timbuktu, which is probably the most important political, economic and cultural center of the Western Sub-Saharan Africa since 13th century on. The mostly considered author of theTaʾrīj al-Fa ttāš, Maḥmūd Kāti, was part of this family. This chronicle is an essential source for the knowledge of the history of which Medieval Arabian writers called Bilād al-Sūdān, the Country of Black People. The aim of this article is to review the tradition kept within the family, that Maḥmūd Kāti’s father, descendant of a very old Andalusi lineage, settled in Western Sudan in the last third of 15th century, coming from the Iberian Peninsula.